Pengembangan Media Puzzle Terhadap Hasil Belajar Pada Tema 8 Subtema 1 Pembelajaran 2 Siswa Kelas III di Sekolah Dasar - Nurhayati Nurhayati (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to determine the development of puzzle media on the learning outcomes of grade III students at SDN 15 Sungai Pinyuh. The research method used is the development research method (Research & Development) while the research model used, namely 4-D with the stages of design, definition, development and dissemination, The subjects in this research are grade III students of SDN 15 Sungai Pinyuh, totaling 45 students consisting of 24 male students and 21 female students. The validation technique used is in the form of collecting data on learning outcome tests. In data collection, a material expert validation questionnaire, student response questionnaire and tests were used. The feasibility results of the Puzzle media are through validation from media experts and material experts. The validation of media experts obtained a total score of 89.5% with the category